Processamento da amêndoa do Butiá (Butia odorata) por tecnologias sustentáveis e integradas para extração de óleo e hidrólise do coproduto sólido - Gallon, Roger (2024)
Palms of the Arecaceae family in 2019 already represented 41.43% of vegetable oil source in the world and, currently, butia is available in vast areas of the southern regions of Brazil to partially supply this demand. With the interest in diminishing biomass residues in order to generate sustainable incomes, the objective of this study is to develop an integrated processing of jelly palm’s kernel, Butia odorata (Barb. Rodr.) Noblick, and evaluate its potential to produce new value-added products. .Supercritical fluid extraction with CO2 followed by subcritical water hydrolysis of the solid residue aiming for fermentable sugars, and Microwave assisted ethanol extraction followed by enzymatic hydrolysis of the solid coproduct aiming also for fermentable sugars were tested. Oil’s yield and quality were evaluated through extraction kinetic curves, fat acids profile and antioxidant activity. Hydrolysis was characterized with kinetic curves in different experimental conditions. The hydrolysates were analyzed with High Performance Liquid Chromatography for sugars, organic acids and fermentation inhibitors yield. The solid coproduct free of extractives was analyzed for centesimal composition, cellulose, hemicellulose and lignin content. Soxhlet extraction with hexane resulted in 40.02 ± 1.14 wt.% (wet basis) of oil high contents of Lauric acid Linoleic acid. Soxhlet extraction with ethanol showed an inhibition percentage 34.24% by antioxidant activity assay. The best sugars yield for subcritical water hydrolysis was 5,78 g/100g of biomass and 2.90 ± 0.24 g/100g, respectively at 260°C and a solvent to feed (S/F) ratio of 50. With microwave extraction, best oil recovery was 81.30 ± 2.15% (60°C-S/F 100) and 85.23 ± 2.09% (80°C-S/F 100). Enzymatic hydrolysis presented similar results for sugars when compared with other works using similar biomasses, with the best result being 66.41 ± 0.40 g/100g at 26 filter paper units (FPU) and concentration of substrate (CS) of 1% in 72 h. It has been demonstrated the economic potential in this agricultural residue which is currently being discarded or underused in producing a high-quality oil for food purposes as secondary products from its purification or conversion of its extraction residue. The collected data, in accordance with other works described, corroborated that sustainable exploitation of jelly palm can diminish biomass wastes, promote economic and social regional development and stimulate consciousness for ecological preservation of the species.